Diamondoids are not forever: microbial biotransformation of diamondoid carboxylic acids. Issue 2 (12th November 2019) - Folwell, Benjamin D.; McGenity, Terry J.; Whitby, Corinne
Summary: Oil sands process‐affected waters (OSPW) contain persistent, toxic naphthenic acids (NAs), including the abundant yet little‐studied diamondoid carboxylic acids. Therefore, we investigated the aerobic microbial biotransformation of two of the most abundant, chronically toxic and environmentally relevant diamondoid carboxylic acids: adamantane‐1‐carboxylic acid (A1CA) and 3‐ethyl adamantane carboxylic acid (3EA). We inoculated into minimal salts media with diamondoid carboxylic acids as sole carbon and energy source two samples: (i) a surface water sample (designated TPW) collected from a test pit from the Mildred Lake Settling Basin and (ii) a water sample (designated 2 m) collected at a water depth of 2 m from a tailings pond. By day 33, in TPW enrichments, 71% of A1CA and 50% of 3EA was transformed, with 50% reduction in EC20 toxicity. Similar results were found for 2 m enrichments. Biotransformation of A1CA and 3EA resulted in the production of two metabolites, tentatively identified as 2‐hydroxyadamantane‐1‐carboxylic acid and 3‐ethyladamantane‐2‐ol respectively. Accumulation of both metabolites was less than the loss of the parent compound, indicating that they would have continued to be transformed beyond 33 days and not accumulate as dead‐end metabolites. There were shifts in bacterial community composition during biotransformation, with Pseudomonas species, especially P. stutzeri, dominating enrichments irrespective of the diamondoid carboxylic acid. In conclusion, we demonstrated the microbial biotransformation of two diamondoid carboxylic acids, which has potential application for their removal and detoxification from vast OSPW that are a major environmental threat. Abstract : Microbes from OSPW aerobically transformed two model diamondoid carboxylic acids. 2‐hydroxy adamantane‐1‐carboxylic acid, and 3‐ethyl adamantane‐2‐ol were produced. Toxicity reduced during microbial biotransformation of diamondoid carboxylic acids. Pseudomonas potentially involved in diamondoid carboxylic acid transformation.